2020
DOI: 10.1097/spv.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vaginal Lactobacillus Species on Escherichia coli Growth

Abstract: Objectives Lactobacillus probiotics have been proposed as an antibiotic-sparing prevention strategy for urinary tract infections (UTIs). Our objective was to examine the relative ability of the 4 most common vaginal Lactobacillus species to inhibit the growth of Escherichia coli, the most common cause of UTIs. Methods Conditioned media (CM) was created from 4 laboratory strains of Lactobacillus species: Lactobacillus cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…For instance, we previously observed that Lactobacillus crispatus is frequently in the urobiomes of women with no LUTS ( Pearce et al, 2014 ). Prior studies have found that Lactobacilli can inhibit the growth of E. coli ( Atassi et al, 2006 , 2019 ; Cadieux et al, 2009 ; Hudson et al, 2020 ). In contrast, E. faecalis can promote E. coli growth under conditions for which it would otherwise not be able to thrive ( Keogh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we previously observed that Lactobacillus crispatus is frequently in the urobiomes of women with no LUTS ( Pearce et al, 2014 ). Prior studies have found that Lactobacilli can inhibit the growth of E. coli ( Atassi et al, 2006 , 2019 ; Cadieux et al, 2009 ; Hudson et al, 2020 ). In contrast, E. faecalis can promote E. coli growth under conditions for which it would otherwise not be able to thrive ( Keogh et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Lactobacillus species L. crispatus , L. gasseri , L. iners , and L. jensenii are predominant members of the “healthy” female urogenital microbiota ( 1 , 2 ). L. jensenii has been shown to be a protective species, reducing growth of uropathogenic Escherichia coli and sexually transmitted infections ( 3 6 ). Recently, Rocha et al ( 7 ) presented a new Lactobacillus species, L. mulieris .…”
Section: Observationmentioning
confidence: 99%
“…The common vaginal Lactobacillus species were used to investigate the inhibition of E. coli growth. The results showed that when L. crispatus was incubated with clinical E. coli strains, the growth of E. coli was inhibited in the acidic environment [112]. Wolff et al studied the changes in the ratio between uropathogens and Lactobacillus (U/L) within the lower UTI in response to oral probiotic supplementation.…”
Section: Probioticsmentioning
confidence: 99%